Pengaruh Sales Promotions terhadap Online Impulse Buying Survei pada Konsumen Gofood di Instagram Gofood Indonesia - Girang Razati; Alifya Putri Maharani Sondra; Ratih Hurriyati (Journal of Business Management Education (JBME), 2023)
This study aims to find out how much Sales Promotions influence Online Impulse Buying for Gofood consumers on Instagram Gofood Indonesia. The type of research used is descriptive and verification. The independent variable in this study is sales promotion (X) and the dependent variable is online impulse buying (Y). Sampling in this study used simple random sampling (random sampling) of 390 respondents. The instrument test was used to test the validity and reliability tests as well as the analytical technique used, namely simple linear regression analysis with SPSS 25.0 for windows software tools. The findings in this study indicate that there is a significant influence from sales promotion on online impulse buying.